2015
DOI: 10.1039/c5tc02308d
|View full text |Cite
|
Sign up to set email alerts
|

High performance electrochromic devices based on a polyindole derivative, poly(1H-benzo[g]indole)

Abstract: An ECD based on electrochromic poly(1H-benzo[g]indole) was fabricated. The color of this ECD can switch between green and navy blue with good optical contrast, high coloration efficiency, fast response time, better optical memory and long-term stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 63 publications
0
20
0
1
Order By: Relevance
“…The EC materials coated to the transparent conducting electrode can change their optical properties reversibly and continuously by applying a small electric potential. Thus, the [89][90][91][92] organics such as Prussian blue, small organic molecule [93][94][95][96][97] including conjugated polymers, [96][97][98][99] transition metal complexes, 34,40,79,[100][101][102][103][104] viologens 105 and conducting polymers. [106][107][108][109] have been examined recently.…”
Section: Electrochromismmentioning
confidence: 99%
“…The EC materials coated to the transparent conducting electrode can change their optical properties reversibly and continuously by applying a small electric potential. Thus, the [89][90][91][92] organics such as Prussian blue, small organic molecule [93][94][95][96][97] including conjugated polymers, [96][97][98][99] transition metal complexes, 34,40,79,[100][101][102][103][104] viologens 105 and conducting polymers. [106][107][108][109] have been examined recently.…”
Section: Electrochromismmentioning
confidence: 99%
“…For example, poly(1H‐benzo[g]‐indole) (PBIn) showed an enhanced coloration efficiency. [ 51 ] Upon application of a 1.5 V bias, PBIn shows an EC color change from gray (neutral) to pale green (oxidized). The monomer of PBIn has a benzo‐moiety, which increases the molecular conjugation and improves the stability of the doped states of PBIns.…”
Section: Electrochromism In Conjugated Polymersmentioning
confidence: 99%
“…The electrochromic properties of PIn were firstly mentioned by Maarouf and coworkers . Recently, our group reported electrochromic properties of poly(1H‐benzo[g]indole), poly(indole‐6‐carboxylic acid), and poly(5‐formylindole) . Spectroelectrochemical studies showed that the dual‐type ECD based on PIns had fast response time, high optical contrast and coloration efficiency (CE), providing an avenue of the PIn family.…”
Section: Introductionmentioning
confidence: 99%
“…24 Recently, our group reported electrochromic properties of poly(1H-benzo[g]indole), poly(indole-6-carboxylic acid), and poly(5-formylindole). [25][26][27] Spectroelectrochemical studies showed that the dual-type ECD based on PIns had fast response time, high optical contrast and coloration efficiency (CE), providing an avenue of the PIn family. The design and synthesis of new electrochromic polymers with different colors and good stabilities still attract great attention due to their potential applications in ECD, LED, and photovoltaic devices.…”
mentioning
confidence: 99%